Design and fabrication of a realistic anthropomorphic heterogeneous head phantom for MR purposes - Wood, Sossena; Krishnamurthy, Narayanan; Santini, Tales; Raval, Shailesh; Farhat, Nadim; Holmes, John Andy; Ibrahim, Tamer S. (PLOS ONE, 2017)
Objective The purpose of this study is to design an anthropomorphic heterogeneous head phantom that can be used for MRI and other electromagnetic applications. Materials and methods An eight compartment, physical anthropomorphic head phantom was developed from a 3T MRI dataset of a healthy male. The designed phantom was successfully built and preliminarily evaluated through an application that involves electromagnetic-tissue interactions: MRI (due to it being an available resource). The developed phantom was filled with media possessing electromagnetic constitutive parameters that correspond to biological tissues at ~297 MHz. A preliminary comparison between an in-vivo human volunteer (based on whom the anthropomorphic head phantom was created) and various phantoms types, one being the anthropomorphic heterogeneous head phantom, were performed using a 7 Tesla human MRI scanner. Results Echo planar imaging was performed and minimal ghosting and fluctuations were observed using the proposed anthropomorphic phantom. The magnetic field distributions (during MRI experiments at 7 Tesla) and the scattering parameter (measured using a network analyzer) were most comparable between the anthropomorphic heterogeneous head phantom and an in-vivo human volunteer. Conclusion The developed anthropomorphic heterogeneous head phantom can be used as a resource to various researchers in applications that involve electromagnetic-biological tissue interactions such as MRI.